Relationship between molecular structure and lamellar and crystalline structure of rice starch. (15th April 2021) - Zhong, Yuyue; Li, Zhihang; Qu, Jianzhou; Bertoft, Eric; Li, Ming; Zhu, Fan; Blennow, Andreas; Liu, Xingxun
Highlights: ACL of fb1 chains positively correlated with lamellar and crystalline order. ACLfb1 and RCfb2 positively correlated with amorphous lamellar thickness. Higher ACLfb3 contributed to more amorphous materials and less double helices. Higher single helix amounts resulted in lower crystalline and lamellar order. Abstract: The relationship between molecular structure and crystalline and lamellar structures of fifteen types of rice starches was studied. GPC and HPAEC were used for the molecular chain analysis and WAXS, SAXS, and CP/MAS 13 C NMR were employed for aggregation structural analysis. The amylopectin content and the average lengths of fb1 -chains (the degree of polymerization (DP) 13–24) were positively correlated with the amount of double helices ( r 2 = 0.92 and 0.57, respectively). In contrast, amylose content was positively correlated with the amounts of amorphous materials in starch ( r 2 = 0.77). The amount of double helices, which constitute a major part of the crystalline matrix, was positively correlated with the lamellar ordering ( r 2 = 0.81), and negatively correlated with the thickness of crystalline lamellae ( r 2 = 0.90) and lamellar repeat distance ( r 2 = 0.84). Conversely, the amount of the amorphous matrix was correlated with these parameters in the opposite way ( r 2 = 0.50, 0.75, and 0.75, respectively).